A holistic approach in developing an ensemble mobile peer-to-peer computing - Che Mohamed Arif, Ahmad Suki; Hassan, Suhaidi; Nisar, Kashif; Habbal, Adib M. Monzer; Omar, Hasbullah; Ismail, Mahamood (2013)
The tremendous growth of mobile computing in recent years has created a lot of interesting potentials for digital economy activities.However, the mobile computing constitutes of various complexities in many forms or types.These heterogeneity have posed various challenges in creating an ensemble environment where multiple heterogeneous mobile devices can communicate smoothly and coherently.These include various mobile platforms, battery life-time, screen sizes, radio access technologies, etc.Couple with other mobile platform requirements; security, forensic tool, resource management, mobile application support, etc. will create great challenges in developing digital economy applications in an ensemble mobile peer-to-peer platform.This paper presents significant issues in our holistic approach of overcoming these challenges.We also elaborate our ideas and plans in approaching some challenges of the issues in this ensemble mobile computing. We also suggest a couple of application development supports for mobile peer-to-peer communication environment.